7 We need support!. (16th April 2018) - Hörberg, A; Jirwe, M; Kalén, S; Vicente, V; Lindström, V
Abstract : Aim: New and inexperienced emergency medical service (EMS) professionals lack important experience. To prevent medical errors and improve retention there is an urgent need to identify ways to support new professionals during their first year in the EMS. Method: A classical Delphi technique in four rounds was used. A purposeful sample and snowball technique was used and generated an expert panel of 32 registered nurses with 12–36 months of EMS experience. In round one telephone interviews were undertaken to identify what support professionals new to the EMS desire during their first year. Content analysis of the transcribed interviews yielded 70 items which were developed into a questionnaire. In subsequent three rounds the experts graded each item in terms of perceived importance on a 5-graded likert scale. Consensus level was set at 75 percent. Results: Desirable support was categorised into eight areas: Support from practical skills exercises, support from theoretical knowledge, support from experiences based knowledge, theoretical support, support from an introduction period, support from colleagues and work environment, support from management and organisation and other support. The experts agree on the level of importance on 64 items regarding desirable support. Of these, 63 items were considered important, graded 4 or 5. One item was considered not important, graded 1 or 2. Conclusion: Even with requested formal competence of the professionals, the EMS context poses challenges where a wide variety of desirable forms of support is needed. Support structures should address both personal and professional levels and be EMS context oriented. Conflict of interest: None Funding: Academic EMS in Stockholm.